Realist evaluation of three programmes aimed at reducing harm and risks associated with alcohol consumption in the Nouvelle Aquitaine region of France: the ECIAE study protocol - Stevens, Nolwenn; Martin-Fernandez, Judith; Moriceau, Sarah; Serre, Fuschia; Auriacombe, Marc; Cambon, Linda (BMJ open, 2022)
IntroductionIn Europe, alcohol consumption is responsible for many diseases, disabilities, injuries and premature deaths. In France, alcohol consumption represents an important health burden, due to its frequency, scale and the serious damage it causes. One of the keys to addressing the problem would appear to be the adoption of harm and risk reduction approaches. In order to operationalise this strategy, the Nouvelle Aquitaine Regional Health Agency is funding three different programmes to reduce the harm and risks associated with alcohol consumption: Alcochoix, Iaca and ETP (Education Thérapeutique du Patient) Conso-repère. We are interested in understanding how, under what circumstances, through which mechanisms and for which population the different programmes work.Methods and analysisThe ECIAE study (a cross-evaluation of the 3 programs Iaca/Alcochoix/ ETP (Patient Therapeutic Education) is a theory-based evaluation where the realist evaluation method is used to explore effects, intervention mechanisms and the influence of context on outcomes. This realist evaluation is based on multiple case studies in two nested levels. At the first level, each centre implementing the programme will represent a case. At the second level, each programme will represent a case in which a set of activities is conducted to achieve risk reduction objectives.Ethics and disseminationThe project will be carried out in full compliance with existing legislation and international conventions. It was subject to analysis, including a privacy impact assessment conducted by the Data Protection Officer of the University of Bordeaux. The University of Bordeaux has ensured that all the regulatory procedures related to the ECIAE study have been carried out. The dissemination plan includes scientific papers, seminars, a report and recommendation and a public restitution. The study will provide evidence-based results to help health authorities roll out strategies to reduce risks and harm associated with alcohol use.